The given equation is
![\sqrt[3]{1+x+√(1+2x)}=2](https://img.qammunity.org/2023/formulas/mathematics/college/g66a6itr38laovs8expufw89p0wtt1w9gl.png)
First, we need to elevate each side to the third power.
![\begin{gathered} (\sqrt[3]{1+x+√(1+2x)})^3=(2)^3 \\ 1+x+√(1+2x)=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/og405ivifzmglrqinl96f2j4i171rmvnor.png)
Second, subtract x and 1 on both sides.
![\begin{gathered} 1+x+√(1+2x)-x-1=8-x-1 \\ √(1+2x)=7-x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xx6yafgt2c6m9p8weo4kly7emrby6zks60.png)
Third, we elevate the equation to the square power to eliminate the root
![\begin{gathered} (√(1+2x))^2=(7-x)^2 \\ 1+2x=(7-x)^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lrw0xg7b4n10uhb50kuvyl7mgyiudvoaid.png)
Now, we use the formula to solve the squared binomial.
![(a-b)=a^2-2ab+b^2](https://img.qammunity.org/2023/formulas/mathematics/college/ga8zawzutelyxddjewzlssudryndvc7szu.png)
![\begin{gathered} 1+2x=7^2-2(7)(x)+x^2 \\ 1+2x=49-14x+x^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ouke7a4u4tlm7kl4gtd618jllgmx0nn9vw.png)
Now, we solve this quadratic equation
![\begin{gathered} 0=49-14x+x^2-2x-1 \\ x^2-16x-48=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3ut03vkf50pezjn3tfag4ix86vravsce14.png)
We need to find two number which product is 48 and which difference is 16. Those numbers are 12 and 4, we write them down as factors.
![x^2-16x-48=(x-12)(x+4)](https://img.qammunity.org/2023/formulas/mathematics/college/x6mar4s3edbbyiw3ufe1zl0ayn8vrzdpcj.png)
So, the possible solutions are
![\begin{gathered} x-12=0\rightarrow x=12 \\ x+4=0\rightarrow x=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ad3yazyjjltrebpf7wni4ijaivtn53q3ex.png)
However, we need to verify each solution to ensure that each of them satisfies the given equation. We just need to evaluate it with those two solutions.
![\begin{gathered} \sqrt[3]{1+x+√(1+2x)}=2\rightarrow\sqrt[3]{1+12+√(1+2(12))}=2 \\ \sqrt[3]{13+√(1+24)}=2 \\ \sqrt[3]{13+√(25)}=2 \\ \sqrt[3]{13+5}=2 \\ \sqrt[3]{18}=2 \\ 2.62=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d5s8fisfpr35nysieoc7ggp6cu0bkkxb9h.png)
As you can observe, the solution 12 doesn't satisfy the given equation.
Therefore, the only solution is -4.